The Influence of Cartoon Film Media on Listening Skills of Elementary School 106865 Bandar Pamah - Rahayu, Rizki Dede (Journal of Elementary School Education, 2024)
This study aims to determine whether there is an effect of using cartoon film media on the listening skills of class III students of elementary school 106865 Bandar Pamah and to determine the learning outcomes before and after using cartoon film media. The method in this study uses quantitative with a one group pretest posttest design model by collecting data using test administration. The data analysis techniques used are validity tests, reliability tests, normality tests, hypothesis tests, and t-tests. The results of the t-test used to test the average value before and after treatment is given whether there is a significant effect or not. Based on the output of "Test Statistic" it is known that the calculated t this value. Where the t table value with a significance level of ɑ = 0.05 is obtained a t table value of6,4281,729.This means that the calculated t value > t table value or > 1.729.6,428thatThere is a significant influence of the use of cartoon film learning media on the story listening skills of students in class III at SD Negeri 106865 Bandar Pamah. So it can be concluded that the hypothesis is accepted (H0 is rejected and Ha is accepted), meaning